(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study investigated employee coordination practices and the job performance of secretaries in federal universities in South-West, Nigeria. the. Descriptive survey design was adopted for the study. Population of the study comprise 500 secretaries in the six federal universities in South-west, Nigeria. These universities are: University of Ibadan, Ibadn, Oyo State, University of Lagos, Akoka, Lagos State, Federal University of Agriculture, Abeokuta, Ogun State, Obafemi Awolowo University, Ile-Ife, Osun State, Federal University of Technology, Akure, Ondo State and Federal University, Oye-Ekiti, Ekiti State. The stratified proportionate sampling technique was used to select 217 using Krejcie and Morgan sample size table. The instrument that was used for data collection in this study was questionnaire with reliability coefficient of 0.93 for Job Performance; 0.93 for Employee Coordination Practices. A total of 217 copies of the questionnaires were administered to the respondents while a total of 215 were retrieved from the field and this represents 99.0% of response rate. Descriptive statistics of frequency counts, simple percentages, mean and standard deviation were used to analyse Research Questions 1, 2, inferential statistics (regression analysis) was used to test the hypotheses formulated at 0.05 level of significance. The level of job performance of secretaries in federal universities in South-west, Nigeria is moderate (Mean = 2.14), roles and responsibilities, participation in decision making and transparency are the employee coordination practices that exist among secretaries in federal universities in South-west, Nigeria, there was a significant influence of the independent variable (employee’s coordination practices) on job performance, F (3, 211) = 67.476, P<0.05, employee coordination practice combined accounted for 48.2% (Adj.R2= .482) variance in the prediction of job performance. it was concluded that employee coordination practices contribute significantly to job performance of secretaries in federal universities in South-west based on the findings it was recommended employee coordination practices should be properly implemented among universities for the secretaries to be effective in their job performance.